Tzanck Smears and Its Diagnostic Utility - An Institutional Experience - Kumar K.T, Dr. Athulya Krishna; Aboobacker, Dr. Kalathingal Kamarunisha; H.S, Dr.Kiran; Agarwal, Dr. Vishal (International Journal of Innovative Research in Medical Science, 2018)
Aim: Tzanck smear is a simple test that gives reliable information in many varieties of skin lesions and can be used for quick, preliminary diagnosis of a number of cutaneous dermatoses. The aim of this study was to analyse the usefulness of tzanck smears in the diagnosis of cutaneous dermatoses and correlate the findings, clinically as well as histopathologically. Materials and Methods: Retrospective analysis of all tzanck smears received during the time period of 2 years (January 2016- January 2018), was carried out. The smears were assessed with regard to its correlation to the clinical diagnosis. Corroboration of the tzanck smear findings were also evaluated with respect to the histopathological diagnosis, in cases were skin biopsy was done. Results: A total of 70 tzanck smears were performed during our study period. Out of 29 cases of pemphigus, the tzanck smears corroborated with 22 cases. Non-specific findings were obtained in clinically suspected cases of pemphigoid. Out of 25 suspected herpetic infections, the characteristic tzanck smear findings were observed in 11 of them. Tzanck smear findings correlated with 13 out of the 19 cases of histopathologically confirmed pemphigus lesions. Conclusion: Tzanck smear test is a rapid, inexpensive and useful tool to aid in the diagnosis of clinically suspected vesico bullous, pustular and erosive skin lesions. It also serves as a useful adjunct to histopathological evaluation of skin biopsies, especially immuno-bullous skin disorders.